Home Security System with Monitoring using Cellular Phone Network - Tri Rahajoeningroem (Program Studi Teknik Elektro, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2013)
This research designed a home security system system with monitoring using cellular phonenetwork. This tool is designed for easy homeowner in the house and locking the door to notice thecondition of the house when the door was left empty, the medium used is a mobile phone by using SMS facility. This device consists of a sensor is a magnetic switch that serves as an input to tell the condition of the door to the microcontroller, ATmega8535 microcontroller is used. Then the keypad which serves as input a password and a GSM modem that serves as a SMS sender and receiver. This security system has been built on the principle if there are people who do not have a password / access code as an entry into the house, then the system will activate the warning / alarm by sounding a warning buzzer and send SMS text notification of the